2022
DOI: 10.1038/s41598-022-17377-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementary light on the photosynthetic apparatus of strawberry plants under salinity and alkalinity stress

Abstract: Considering the destructive effect of stresses on the photosynthetic apparatus of plants and the important role of light in photosynthesis, we investigated the effect of complementary light on the photosynthetic apparatus under salinity and alkalinity stress conditions. Light-emitting diodes (LEDs) in monochromatic blue (460 nm), monochromatic red (660 nm), dichromatic blue/red (1:3), white/yellow (400–700 nm) at 200 μmol m−2 S−1, and without LED treatment were used. The stress treatments were in three stages:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The rapid ChlF test was developed specifically as a biophysical tool for evaluating the cascade of chloroplast redox reactions at microsecond or millisecond scales ( Kalaji et al., 2016 ; Esmaeilizadeh et al., 2021 ; Sharma et al., 2021 ; Shamsabad et al., 2022a ; Sieczko et al., 2022 ; Dąbrowski et al., 2023 ). The link between the physiological condition of samples and the fluorescence transient has also been the subject of important empirical research in the past, including demonstrating the direct or indirect association between the physiological state of leaves and ChlF transients.…”
Section: Limitationsmentioning
confidence: 99%
“…The rapid ChlF test was developed specifically as a biophysical tool for evaluating the cascade of chloroplast redox reactions at microsecond or millisecond scales ( Kalaji et al., 2016 ; Esmaeilizadeh et al., 2021 ; Sharma et al., 2021 ; Shamsabad et al., 2022a ; Sieczko et al., 2022 ; Dąbrowski et al., 2023 ). The link between the physiological condition of samples and the fluorescence transient has also been the subject of important empirical research in the past, including demonstrating the direct or indirect association between the physiological state of leaves and ChlF transients.…”
Section: Limitationsmentioning
confidence: 99%
“…The use of rootstocks can increase the total soluble solids and nutritional status of grapevine fruits grown in alkaline environments [51]. In contrast, the use of light-emitting diodes in monochromatic blue (460 nm), monochromatic red (660 nm), and dichromatic blue/red (1:3) light at 200 μmol m À2 s À1 enhances electron transport per reaction center and the probability of transferring electrons from the exciton into the electron transport system, promoting gas exchange in alkalinity-stressed strawberry plants [47,99].…”
Section: Alkalinity Management Strategiesmentioning
confidence: 99%
“…It was suggested that B light significantly increases plant tolerance to alkaline stress through various physiological and biochemical mechanisms [2,44]. When exposed to B light, plant photoreceptors, such as cryptochromes and phototropins, are activated, initiating a signaling cascade that triggers responses to combat alkaline stress [44].…”
Section: Blue Light and Gaba Enhanced Tolerance Mechanisms Against Al...mentioning
confidence: 99%
“…In this pursuit of resilient agriculture, a particular stressor that warrants attention is alkalinity stress [1]. Alkaline soil and irrigation water conditions can severely hamper plant growth and productivity [1,2]. Excessive alkalinity in water can disrupt the delicate pH balance essential for proper nutrient uptake in plants, leading to nutrient deficiencies and reduced growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation